Implication of Refocusing Policy on Education Financing In State Islamic Universities During Covid-19 Pandemic - Yayuk Sri Rahayu (Department of Public Administration, 2022)
A budget is an important tool for the government to implement its programs, which are more or less influenced by budget management. The state budget reflects the policy decisions between the executive and the legislature that describe what the government does each year. This political decision has a major impact on people's living standards, especially in terms of better fulfilling the basic needs of citizens. As is understood, a policy always has a purpose. In the context of these objectives, it is hoped that every substance of public policy will always be useful for fulfilling the interests of the people. It's just that in the context of benefits, each public policy provides different benefits for various community groups. The greatest benefits of a public policy tend to be enjoyed by the initiator of public policy. This study was conducted to examine the effect of government policies with adjustments to the management of education funds at State Islamic Universities during the pandemic. This research method is to cite qualitative data from various primary and secondary literature. Informants as data sources and actors who contribute to the success or failure of an investigation based on the information provided. Based on the results of the study that the refocusing policy greatly influences education financing during the pandemic, this is evidenced by the reallocation of several activity programs which at the beginning of the year had been prepared to allocate several programs related to the handling of covid 19.